Exposure to airborne particulate matter in Kathmandu Valley, Nepal - Gurung, Anobha; Bell, Michelle L (Journal of exposure science & environmental epidemiology, 2012)
Kathmandu Valley, Nepal, has severe air pollution, although few studies examine air pollution and health in this region. To the best of our knowledge, no previous studies in Nepal used time-activity diaries or conducted personal monitoring of individuals’ exposures. We investigated personal exposure of particulate matter (PM) with aerodynamic diameter ≤2.5 μ m (PM 2.5 ) by location, occupation, and proximity to roadways. PM 2.5 monitoring, time-activity diary, respiratory health questionnaire, and spirometer testing were performed from 28 June 2009 to 7 August 2009 for 36 subjects, including traffic police (TP), indoor officer workers next to main road (IOWs_NMR) and away from main road (IOWs_AMR), in urban area (UA), urban residential area, and semi-UA (SUA). TP had the highest exposure of all the occupations (average 51.2 μ g/m 3 , hourly maximum >500 μ g/m 3 ). TP levels were higher at the UA than other locations. IOW_NMR levels (averaged 46.9 μ g/m 3 ) were higher than those of IOW_AMR (26.2 μ g/m 3 ). Exposure was generally higher during morning rush hours (0800–1100 hours) than evening rush hours (1500–1800 hours) for all occupations and areas (78% of days for TP and 84% for urban IOW). PM 2.5 personal exposures for each occupation at each location exceeded the World Health Organization ambient PM 2.5 guideline (25 μ g/m 3 ). Findings suggest potential substantial health impacts of air pollution on this region, especially for TP.